Iogurte em barra: desenvolvimento e caracterização - Santos, Jucenir dos (2021)
Yogurt is the most consumed fermented milk in the world, but its shelf life is relatively short compared to other dairy products. And although drying the yogurt increases its shelf life and reduces its operating costs in terms of maintaining the cold chain, transport and storage, its use in the original form of yogurt still requires the consumer to use chilled water to rehydrate the yogurt. same. In this way, the present work had as objective the development of a solid form of yogurt, for ready consumption and without the need for refrigeration from transport to final consumer. With a huge innovative character, yogurt bars are an alternative in the dairy sector that seeks to solve the problem of reducing operational costs of maintaining the cold chain while offering convenience to the end consumer. Initially, natural yogurt was developed, after production 4 formulations were prepared: F1: Only the ingredients from the yogurt fermentation; F2: F1 ingredients, plus 10% maltodextrin; F3: F1 ingredients, plus 0.2% lecithin and F4: F1 ingredients, plus 10% maltodextrin and 0.2% lecithin. All formulations were dried in a tray freeze dryer for 48 hours. Then they were crushed and shaped into a bar. After the elaboration of yogurt bar, physical characterization (Solubility, total dry extract, humidity and scanning electron microscopy), chemical (acidity, pH, ash, DSC, volatile compounds, proteins, lipids, carbohydrates, energy value) were carried out and microbiological (lactic acid bacteria, molds and yeasts, Salmonella, thermotolerant coliforms). The experiments were carried out in triplicate, and the results obtained were evaluated by analysis of variance (ANOVA) and the means compared by the Tukey test at 5% probability, using the Sisvar software. With regard to physical and chemical analysis, there was a significant difference (p <0.05) for all parameters evaluated, with the exception of pH and lipid content. The results showed that yogurt bar is a food with a high content of proteins and lipids. Low moisture content when compared to bar food, and lower caloric content than conventional yogurt. All formulations had a lactic acid bacteria count of more than 107 UFC / g, classifying them as yogurt. No formulation presented a count of Salmonella, E. coli and molds and yeasts above that established by RDC 331/2019, showing no contamination. The addition of maltodextrin and lecithin in the formulation improved parameters of solubility and thermal stability showing positive effects on their addition. Formulation 4 was considered the most suitable for future work and large-scale production.